2005
DOI: 10.1097/01.rli.0000153930.34439.e4
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of End-Systole for Optimal Reconstruction Protocol of Coronary Angiography With 16-Slice Multidetector Computed Tomography

Abstract: Combining ES and MD reconstructions reduces nonevaluable coronary arteries, particularly with higher heart rates. A protocol including 2-3 reconstructions is the most efficient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 38 publications
0
23
0
3
Order By: Relevance
“…25 Using a technique termed retrospective image reconstruction, images can be reconstructed at any point in the cardiac cycle. 29,30 Although several types of reconstruction algorithms exist, a proposed optimal reconstruction window for motion-free visualization of the coronary arteries is in mid diastole at 60% to 70% of the R-R interval. 30 Three dimensional volume rendered color images show surface anatomy (figure 1).…”
Section: Image Reconstruction and Interpretationmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Using a technique termed retrospective image reconstruction, images can be reconstructed at any point in the cardiac cycle. 29,30 Although several types of reconstruction algorithms exist, a proposed optimal reconstruction window for motion-free visualization of the coronary arteries is in mid diastole at 60% to 70% of the R-R interval. 30 Three dimensional volume rendered color images show surface anatomy (figure 1).…”
Section: Image Reconstruction and Interpretationmentioning
confidence: 99%
“…29,30 Although several types of reconstruction algorithms exist, a proposed optimal reconstruction window for motion-free visualization of the coronary arteries is in mid diastole at 60% to 70% of the R-R interval. 30 Three dimensional volume rendered color images show surface anatomy (figure 1). Three dimensional maximum intensity projection and two dimensional multiplanar reformation are used to see inside the heart and visualize the coronary arteries.…”
Section: Image Reconstruction and Interpretationmentioning
confidence: 99%
“…"Motion artifacts" were defined as any blurring of the normally sharply defined vessel contour. 15,18,19 Poor contrast enhancement, motion artifacts, and streak artifacts were considered to be a direct result of our protocol, whereas tiny vessel size, heavy calcification, and pacemaker artifacts were not. Next, we performed a vessel-level analysis in which each coronary artery in each patient was given an overall image-quality grade.…”
Section: Cardiac Cta Evaluationmentioning
confidence: 99%
“…It has been shown that the optimal reconstruction window in which the coronary arteries can be visualized nearly free of motion artifacts starts in mid-diastole (60%-70% of the R-R interval) (27,28). Exceptions are patients with higher or irregular heart rates, in which a reconstruction window positioned in late systole (25%-35% of the R-R interval) often yields the best image quality.…”
Section: Image Reconstructionmentioning
confidence: 99%